2018
DOI: 10.1016/j.amsu.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Limited distal duodenal resection: Surgical approach and outcomes. A case series

Abstract: IntroductionTumours involving the duodenum are usually treated with pancreaticoduodenectomy, which may be associated with considerable morbidity. Limited distal duodenal resection, a relatively smaller procedure, can be done in some of these patients. We describe our experience with this operation for such lesions.MethodsWe retrospectively analyzed, from prospectively collected data 10 consecutive patients who underwent limited duodenal and proximal jejunal resection between March 2011 and Nov 2015.ResultsTher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
2
2
0
3
Order By: Relevance
“…[6][7][8]11,12,17 Partial and radical resections have not been shown to have different outcomes in terms of obtaining negative margins. 17,20,26,27 This study supports previous findings that worse overall survival was associated with positive surgical margin status. 22,28 This study found that adjuvant therapy appeared to be associated with improved survival.…”
Section: Discussionsupporting
confidence: 90%
“…[6][7][8]11,12,17 Partial and radical resections have not been shown to have different outcomes in terms of obtaining negative margins. 17,20,26,27 This study supports previous findings that worse overall survival was associated with positive surgical margin status. 22,28 This study found that adjuvant therapy appeared to be associated with improved survival.…”
Section: Discussionsupporting
confidence: 90%
“…6) in a majority of our patients because it is technically easy to perform, without the need for sutures on the mesenteric side, and provides a wide stoma. Dorcaratto et al [9], in their series of 11 patients reported additional complications and longer postoperative stay in patients with end-to-side compared with end-to-end anastomoses, while another series of side-to-side duodeno-jejunal anastomoses reported from India [7] did not encounter any leak-related morbidity, similar to our results. It is not possible to comment on the relative superiority of reconstruction techniques because of the limited number of studies including small number of patients investigated.…”
Section: A B C Dsupporting
confidence: 90%
“…El margen distal es preferentemente en el yeyuno, ya que posee vascularización desde la arcada de Rolando y, por lo tanto, tiene menor riesgo de filtraciones anastomóticas en comparación con la porción distal del duodeno de circulación terminal. Esta anastomosis puede ser realizada terminolateral, latero-lateral y termino-terminal, sin haber evidencia suficiente para apoyar una sobre la otra y en general es determinada por cada centro o caso a caso según las condiciones del paciente 3 .…”
Section: Discussionunclassified
“…Las RDD requieren un detallado conocimiento anatómico de la zona, siendo frecuente la necesidad de una adecuada exposición del retroperitoneo a través de las maniobras de Kocher y de Cattell-Braash 3 . Sus indicaciones son variadas, siendo lo más frecuente la patología neoplásica, principalmente GIST duodenal 4 .…”
Section: Introductionunclassified